2015
DOI: 10.1590/0102-33062014abb3534
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of bryophytes in priority areas for conservation in the Atlantic forest of northeast Brazil

Abstract: The northeastern Brazilian Atlantic forest is the region with the greatest diversity of bryophytes in the country. However, knowledge about bryophytes is irregularly distributed among Brazilian regions. Therefore, we aimed to contribute to knowledge about bryophytes on a regional scale in the northeastern Atlantic forest, to identify the centers of bryophyte diversity in that region, and to reiterate the importance and identify locations for which new protected areas should be created. We built a database of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
1
0
4
Order By: Relevance
“…A família Sematophyllaceae é uma das mais diversas no Brasil, com 53 espécies, sendo uma das principais famílias encontrada no domínio fitogeográfico da Mata Atlântica (Costa & Luizi-Ponzo 2010). Outros trabalhos realizados com briófitas em áreas de Mata Atlântica também encontraram essas famílias sendo as mais representativas (Santos & Costa 2008, Valente et al 2009, Silva & Pôrto 2015e Carmo et al 2016.…”
Section: Resultsunclassified
“…A família Sematophyllaceae é uma das mais diversas no Brasil, com 53 espécies, sendo uma das principais famílias encontrada no domínio fitogeográfico da Mata Atlântica (Costa & Luizi-Ponzo 2010). Outros trabalhos realizados com briófitas em áreas de Mata Atlântica também encontraram essas famílias sendo as mais representativas (Santos & Costa 2008, Valente et al 2009, Silva & Pôrto 2015e Carmo et al 2016.…”
Section: Resultsunclassified
“…Para as hepáticas a família Lejeuneaceae se destaca, apresentando 80 espécies, o que representa 35% das hepáticas encontradas nessa área. A família Lejeuneaceae aparece em inúmeros trabalhos como sendo a mais diversa entre as hepáticas para o Estado de São Paulo (Visnadi 2005, Visnadi 2009, Yano & Peralta 2007) e para as demais áreas do Brasil (Valente & Pôrto 2006, Santos & Costa 2008, Costa et al 2011, Reis et al 2015, Silva & Pôrto 2015e Carmo & Peralta 2016. Para o Brasil, estudos apontam que existam aproximadamente 285 espécies de Lejeuneaceae, distribuídos em 55 gêneros (Costa & Peralta 2015a, b) e a Mata Atlântica é o domínio fitogeográfico com o maior número de espécies (246 spp., Flora do Brasil 2020, em prep.…”
Section: Resultados and Discussãounclassified
“…Até o momento, não há estudos de briófitas realizados para o PECJ, o que se conhece da brioflora dessa região é proveniente de citações para o Estado de São Paulo em bibliografias com enfoques florísticos e ecológicos para Mata Atlântica (Costa & Lima 2005, Santos & Costa 2008, Costa & Santos 2009, Santos & Costa 2010, Costa & Peralta 2015b, Silva & Pôrto 2015. O objetivo principal deste estudo é apresentar o levantamento de briófitas mostrando a diversidade do grupo na área do Parque Estadual de Campos do Jordão.…”
Section: Introductionunclassified
“…Assuming that undisturbed habitats are necessary to maintain the diversity of bryophytes in the Atlantic Forest (Silva & Pôrto 2015), legally protected areas are expected to play a fundamental role in the conservation of this group (Brasil 2000). However, recent analyses have shown that only 27% of the total area potentially suitable for the occurrence of key species falls within protected areas established in this biome (Silva et al 2014), which is considered less than adequate for efficient conservation of the group.…”
Section: Introductionmentioning
confidence: 99%